SOCIO-PEDAGOGICAL DISPUTES ON ABILITY TO BE SUBJECT. BETWEEN THE DEPENDENCY AND AUTONOMY - Jordi Planella (Editora da Universidade de Santa Cruz do Sul, 2015)
The article proposes a critical analysis of two categories that operate of notable form in the theories and praxis linked to the Social Pedagogy. It treats to study until which point the subjectivity is called blindly to the idea of autonomy or if by the contrary this can sustentarse in a positive interpretation of the idea of dependency. For this the article does a terminological and pedagogical analysis of his uses and abuses.